2003
DOI: 10.1136/ard.62.11.1078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tumour necrosis factor   antagonists on serum transaminases and viraemia in patients with rheumatoid arthritis and chronic hepatitis C infection

Abstract: Background: Tumour necrosis factor a (TNFa) antagonists are effective for the treatment of rheumatoid arthritis (RA), but concerns remain about the safety of these agents in the presence of chronic infections, including hepatitis C virus (HCV) infection. Objective: To examine the influence of treatment with TNFa antagonists on levels of HCV viraemia and serum transaminases in patients with RA and HCV. Methods: In a retrospective survey the course of 16 HCV infected patients with RA who had received the TNFa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(98 citation statements)
references
References 41 publications
8
83
1
6
Order By: Relevance
“…Evidence from clinical trials suggests that TNF inhibitors are not significantly associated with HCV reactivation. For example, in a study of HCV-infected patients with RA who were treated with infliximab or etanercept, there were no significant differences in liver function test results (n ϭ 24) or in HCV titers (n ϭ 22) from baseline to 34 months (48). In another study, 3 patients with RA and chronic HCV infection experienced no changes in liver enzyme levels or viral load following 6-39 months of TNF inhibitor therapy (49).…”
Section: Hepatitis C Virusmentioning
confidence: 98%
“…Evidence from clinical trials suggests that TNF inhibitors are not significantly associated with HCV reactivation. For example, in a study of HCV-infected patients with RA who were treated with infliximab or etanercept, there were no significant differences in liver function test results (n ϭ 24) or in HCV titers (n ϭ 22) from baseline to 34 months (48). In another study, 3 patients with RA and chronic HCV infection experienced no changes in liver enzyme levels or viral load following 6-39 months of TNF inhibitor therapy (49).…”
Section: Hepatitis C Virusmentioning
confidence: 98%
“…The case series suggest that anti-TNF therapy has no adverse effects and that it might even improve HCV infection. 29,[47][48][49][50][51][52][53][54][55][56] Some authors 57 found no significant differences in liver function or viraemia at baseline or during follow-up in HCV-infected patients receiving infliximab or etanercept for rheumatoid arthritis. Finally, etanercept improved virological response to combined interferon-a plus ribavirin in HCV-positive patients.…”
Section: Effect Of Immunosuppressants On Hcv Infectionmentioning
confidence: 99%
“…Показано, что ФНО-α может индуцировать продукцию бета-факто-ра трансформации роста, экспрессия которого тесно связана с гистологической выраженностью активности процесса и долькового некроза у больных с хронической HCV-инфекцией. Более того, высокие уровни ФНО-α ока-зывают негативное влияние на ответ макроорганизма больного HCV при терапии интерфероном [85]. Следовательно, блокирование ФНО-α могло бы иметь благоприятные последствия для больных с HCV-инфекцией.…”
Section: хронические вирусные гепатитыunclassified